YOGA SAMADHI SEBAGAI UPAYA TERWUJUDNYA MANUNGGALING KAWULA GUSTI (Perspektif Kejawen) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Some of the people on the island of Java who still carry out the rituals and concept ofManunggaling Kawula Gusti are the Kejawen people. Kejawen is a Javanese spiritual beliefthat contains traditions, rituals, as well as art and culture. The Javanese tribe is one of thetribes in Indonesia that has very strong local beliefs in the archipelago so that it has developedand become the soul of its people's lives. In Javanese society, traditions and rituals certainlycannot be put aside because they have become part of their lives in believing in the existenceof God and all its manifestations. The island of Java already has unique Indonesian beliefs andnot religions originating from abroad. This also causes rituals and traditions to exist inJavanese society because of alcuturation. The concept of Manunggaling Kawula Gusti is thecore of Wirid Hidayat Jati's teachings which has the ideals of human life that humans mustachieve, namely gaining an appreciation of unity with God through the path of samadhi. Thereare certain types and procedures, actors, facilities, times and places for doing Samadhi so thatyou can be suwung and Manunggaling Kawula Gusti. Through the success of Yoga Samadhi,humans can recognize the True Teacher as a good life guide and can Manunggaling KawulaGusti. The function of Yoga Samadhi in the Manunggaling Kawula Gusti Concept is as areligious, social and educational function
Keywords: samadhi yoga, unite with god, java